Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\frac{4^{10}.9^6+3^{12}.8^5}{6^{13}.4-2^{16}.3^{12}}\)
\(=\frac{\left(2^2\right)^{10}.\left(3^2\right)^6+3^{12}.\left(2^3\right)^5}{\left(2.3\right)^{13}.2^2-2^{16}.3^{12}}\)
\(=\frac{2^{20}.3^{12}+3^{12}.2^{15}}{2^{13}.3^{13}.2^2-2^{16}.3^{12}}\)
\(=\frac{2^{20}.3^{12}+3^{12}.2^{15}}{2^{15}.3^{12}.3-3^{12}.2^{16}}\)
\(=\frac{2^4}{3}\)
\(\dfrac{4^{10}.9^6+3^{12}.8^5}{6^{13}.4-2^{16}.3^{12}}\)
\(=\dfrac{\left(2^2\right)^{10}.\left(3^2\right)^6+3^{12}.\left(2^3\right)^5}{\left(2.3\right)^{13}.2^2-2^{16}.3^{12}}\)
\(=\dfrac{2^{20}.3^{12}+3^{12}.2^{15}}{2^{13}.3^{13}.2^2-2^{16}.3^{12}}\)
\(=\dfrac{2^{20}.3^{12}+3^{12}.2^{15}}{2^{15}.3^{13}-2^{16}.3^{12}}\)
\(=\dfrac{2^{15}.3^{12}.\left(2^5+1\right)}{2^{15}.3^{13}.\left(3-2\right)}\)
\(=\dfrac{2^5+1}{3-2}\)
\(=\dfrac{32+1}{1}=33\)
Thực hiện phép tính ( bằng cách hợp lí nếu có thể )
A. 2/3 - (- 1/4)+3/5-(+7/45)-(-5/9)+1/12+1/39
B. 6.(-2/3)^2 - 3(-2/3)^2 - 2 : (-3/2)+4
a) \(=\frac{\left(\frac{9}{25}-36\right)}{\frac{19}{5}+\frac{1}{5}}=\frac{\frac{9}{25}-\frac{900}{25}}{\frac{20}{5}}=\frac{-891}{25}:4\)\(=\frac{-891}{25\cdot4}=\frac{-891}{100}=-8,91\)
b) \(=12\cdot\frac{\left(-2\right)^2}{3^2}+\frac{4}{3}=12\cdot\frac{4}{9}+\frac{4}{3}\)\(=\frac{48}{9}+\frac{4}{3}=\frac{48}{9}+\frac{12}{9}=\frac{60}{9}\)
\(S=\dfrac{3}{4}-\dfrac{1}{4}-\left(\dfrac{7}{3}-\dfrac{9}{2}\right)-\dfrac{5}{6}\)
\(=\left(\dfrac{3}{4}-\dfrac{1}{4}+\dfrac{18}{4}\right)-\left(\dfrac{14}{6}+\dfrac{5}{6}\right)\)
\(=\dfrac{20}{4}-\dfrac{19}{6}=\dfrac{11}{6}\)
\(\dfrac{16^3.3^{10}+120.6^9}{4^6.3^{12}+6^{11}}=\dfrac{\left(2^4\right)^3.3^{10}+3.5.2^3.\left(2.3\right)^9}{\left(2^2\right)^6.3^{12}+\left(2.3\right)^{11}}\)
\(=\dfrac{2^{12}.3^{10}+3.5.2^3.2^9.3^9}{2^{12}.3^{12}+2^{11}.3^{11}}=\dfrac{2^{12}.3^{10}+5.2^{12}.3^{10}}{2^{12}.3^{12}+2^{11}.3^{11}}\)
\(=\dfrac{2^{12}.3^{10}\left(1+5\right)}{2^{11}.3^{11}.\left(2.3+1\right)}\)\(=\dfrac{2^{12}.3^{10}.6}{2^{11}.3^{11}.7}=\dfrac{2.2}{7}=\dfrac{4}{7}\)
a. \(\dfrac{-2}{3}+\dfrac{-1}{5}+\dfrac{3}{4}-\dfrac{5}{6}-\dfrac{7}{10}\)
= \(\dfrac{-4}{6}+\dfrac{-2}{10}+\dfrac{3}{4}-\dfrac{5}{6}-\dfrac{7}{10}\)
= \(\dfrac{-3}{2}+\dfrac{1}{2}+\dfrac{3}{4}\)
= (-1) + \(\dfrac{3}{4}\)
= \(\dfrac{-4}{4}+\dfrac{3}{4}\)
= \(\dfrac{-1}{4}\)
b; 0,5 + \(\dfrac{1}{3}\) + 0,4 + \(\dfrac{5}{7}\) + \(\dfrac{1}{6}\) - \(\dfrac{4}{35}\)
= (\(\dfrac{1}{3}\)+ \(\dfrac{1}{6}\) + \(\dfrac{1}{2}\)) + (\(\dfrac{5}{7}\)- \(\dfrac{4}{35}\)+ \(\dfrac{2}{5}\))
= ( \(\dfrac{1}{2}\) + \(\dfrac{1}{2}\)) + (\(\dfrac{3}{5}\) + \(\dfrac{2}{5}\))
= 1 + 1
= 2
(\(\dfrac{2}{9}\) - \(\dfrac{7}{12}\) ): \(\dfrac{3}{4}\)+ ( \(\dfrac{16}{9}\) - \(\dfrac{5}{12}\)) : \(\dfrac{3}{4}\)
= ( \(\dfrac{2}{9}\) - \(\dfrac{7}{12}\) + \(\dfrac{16}{9}\) - \(\dfrac{5}{12}\)) : \(\dfrac{3}{4}\)
= ( \(\dfrac{18}{9}\) - \(\dfrac{12}{12}\) ) : \(\dfrac{3}{4}\)
= (2 -1) : \(\dfrac{3}{4}\)
= 1 : \(\dfrac{3}{4}\)
= \(\dfrac{4}{3}\)